TYPES OF NEIROHUMORAL REGULATION OF BLOOD PRESSURE HOMEOSTASIS DURING TILT-TEST IN HYPERTENSIVE PATIENTS ON THE BASE OF THE HEART RATE VARIABILITY STUDY - Bilchenko, O.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The aim of the study was to estimate types of neirohumoral regulation on the base of the heart rate variability indexes at rest and during tilt-test in hypertensive patients. 176 patients with hypertension were included in the study. The data obtained in this study  shown that in hypertensive patients balans of regulatory brunches or increase of humoral regulation observed more frequently. Dominance of neural regulation associated with favorable prognosis concerning mortality in patients with hypertension. During tilt-test decreased brunches at rest increased.